2020
DOI: 10.1016/j.celrep.2020.107885
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T Cells Recognize Conserved Influenza A Epitopes through Shared Patterns of V-Gene Usage and Complementary Biochemical Features

Abstract: Summary T cell recognition of peptides presented by human leukocyte antigens (HLAs) is mediated by the highly variable T cell receptor (TCR). Despite this built-in TCR variability, individuals can mount immune responses against viral epitopes by using identical or highly related TCRs expressed on CD8 + T cells. Characterization of these TCRs has extended our understanding of the molecular mechanisms that govern the recognition of peptide-HLA. However, few examples exist for CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 69 publications
(110 reference statements)
0
15
0
Order By: Relevance
“…First, we set out to identify any shared biochemical features of these public TCRs which recognize only SARS‐CoV‐2‐HCoV peptides compared with those which recognize only non‐homologous SARS‐CoV‐2 peptides [ 56 , 59 , 60 , 61 , 62 ]. Between these two groups, we observed only minor differences in CDR3 motifs and lengths of these sequences, for which the effect of technical variation could not be ruled out (Figure S5a–d ).…”
Section: Resultsmentioning
confidence: 99%
“…First, we set out to identify any shared biochemical features of these public TCRs which recognize only SARS‐CoV‐2‐HCoV peptides compared with those which recognize only non‐homologous SARS‐CoV‐2 peptides [ 56 , 59 , 60 , 61 , 62 ]. Between these two groups, we observed only minor differences in CDR3 motifs and lengths of these sequences, for which the effect of technical variation could not be ruled out (Figure S5a–d ).…”
Section: Resultsmentioning
confidence: 99%
“…One immunogenic peptide generated from the surface glycoprotein Haemagglutinin (HA), namely HA 306–318 , is able to be presented by multiple HLA-DR alleles [ 62 , 63 ]. Numerous studies have characterised CD4 + T cell responses towards this universal HA 306–318 peptide [ 15 , 64 , 65 ] including their recognition of the pHLA-II complex [ 15 , 16 ]. Two CD4 + TCR structures have been solved in complex with HA 306–318 presented by HLA-II molecules ( Table 1 ) offering insight on how CD4 + TCRs can recognise influenza epitopes.…”
Section: T Helper 1 Cells (Th1)mentioning
confidence: 99%
“…Both structures comprise HLA-DR1 presenting the HA 306–318 peptide. The first structure was published in 2000 [ 16 ] and the second structure more recently in 2020 [ 15 ]. The two TCRs (HA1.7 and F11) share the same TRAV, but different TRBV genes ( Table 1 ), and both TCRs bind to HLA-DR1- HA 306–318 in a canonical docking mode, with a similar number of contacts with the pHLA-II.…”
Section: T Helper 1 Cells (Th1)mentioning
confidence: 99%
“…We further examined pre-existing and vaccine-induced responses to both HA and other influenza viral proteins (NA, M1, M2, NP, NEP, NS1, PA, PB1, and PB2) that may potentially elicit T cell responses [ 12 , 13 ]. Previous studies found that the majority (>80%) of pre-existing CD4 and CD8 T cell responses to influenza A virus strains (H3N2 and H1N1) are directed to the more conserved core proteins (NP/M/NS/PA/PB) and may mediate cross-reactive protection against different influenza A strains [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though extensive studies have reported that both CD4 and CD8 T cells recognize conserved influenza epitopes from viral proteins other than HA [ 12 , 13 ], the study of the cellular immune responses elicited by influenza core protein components in vaccination settings, and particularly in response to Flucelvax immunization are lacking. Hence, studying how non-HA viral proteins contained in Flucelvax contribute to the vaccination response is of interest.…”
Section: Introductionmentioning
confidence: 99%